(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
Administrative and financial corruption has many causes, including political, social, and economic ones. It can be internal or external, leaving profound impacts on the economic and social structure of both developing and developed countries. Administrative and financial corruption has become the greatest enemy of development plans and programs. It has spread backwardness, significantly Impacting all aspects of life and the general activities of citizens, even undermining the political system by emptying It of the foundations of stability. This leads to significant losses of money, effort, and time, as well as missed opportunities for progress and prosperity. Therefore, this research aims to employ governance to combat financial and administrative corruption and reduce poverty by addressing the importance of governance, its indicators, and the forms of financial and administrative corruption. The research concludes that the cost and Impact of financial and administrative corruption are very significant, depriving societies of their right to equality and increasing the suffering of the working class (the poor). The research also highlights the need to raise awareness in society about the importance of governance as a safe haven and a strong shield that protects Institutions from the scourge of financial and administrative corruption.